2011
DOI: 10.1590/s1809-48722011000200006
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between the Peak Nasal Inspiratory Flow and the Visual Analogue Scale Before and After Using a Nasal Decongestant

Abstract: Summary Introduction: The measurement of the peak nasal inspiratory flow (PNIF) is easily and swiftly obtained, but hardly spread in Brazil though. On the other hand, the visual analogue scale (VAS) for nasal obstruction is a subjective measurement that can also be used. Objective: To evaluate the correlation between PNIF and VAS for nasal obstruction before and after occurring a change in the nasal patency caused by the topic vasoconstriction. Study outline: Non-randomized clinical and exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
0
2
0
3
Order By: Relevance
“…No entanto, Marais et al 27 mostraram melhora no Peak Flow após septoplastia, e Cook et al 28 revelaram melhora após tratamento com laser da rinite alérgica. Teixeira et al 11 demonstraram correlação importante entre a medida objetiva da obstrução nasal através do Peak Flow com a mensuração subjetiva proporcionada pela EVA antes e após a vasoconstrição nasal em 60 indivíduos. Resultados semelhantes foram encontrados por Fairley et al, 29 Priftis et al 16 e Wilson et al 30 Todos os pacientes que foram submetidos à septoplastia e turbinectomia neste trabalho apresentavam agravo na sua qualidade de vida, que foi constatado em todas as avaliações realizadas nos pré-operatórios.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…No entanto, Marais et al 27 mostraram melhora no Peak Flow após septoplastia, e Cook et al 28 revelaram melhora após tratamento com laser da rinite alérgica. Teixeira et al 11 demonstraram correlação importante entre a medida objetiva da obstrução nasal através do Peak Flow com a mensuração subjetiva proporcionada pela EVA antes e após a vasoconstrição nasal em 60 indivíduos. Resultados semelhantes foram encontrados por Fairley et al, 29 Priftis et al 16 e Wilson et al 30 Todos os pacientes que foram submetidos à septoplastia e turbinectomia neste trabalho apresentavam agravo na sua qualidade de vida, que foi constatado em todas as avaliações realizadas nos pré-operatórios.…”
Section: Discussionunclassified
“…Também pode ser induzida por medicamentos tópicos e outras drogas ingeridas ou injetadas, além de alterações endócrinas e metabólicas. 4,[11][12][13][14][15] Na obstrução nasal é encontrada deficiência no aquecimento e umidificação do ar inspirado e na própria função filtrante nasal. 9 Além disso, o padrão respiratório é alterado, levando à respiração oral, que está relacionada diretamente a alterações do crescimento facial, fala, distúrbios alimentares, alterações posturais, dificuldades escolares e sociais e doenças do sono, comprometendo consideravelmente a qualidade de vida.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…The VAS is one of the most used measures in pain intensity research 17,18 and, despite major technological advances, it is still the best parameter for assessing pain intensity 6 . It is a linear and multidimensional scale that allows the simple and efficient measurement of pain intensity, as it represents a quick index, in which the patient can indicate a numerical value between 0 and 10—where zero indicates absence of pain and 10 indicates presence of intense pain, enabling quantitative analysis of the data 19 …”
Section: Methodsmentioning
confidence: 99%
“…6 It is a linear and multidimensional scale that allows the simple and efficient measurement of pain intensity, as it represents a quick index, in which the patient can indicate a numerical value between 0 and 10-where zero indicates absence of pain and 10 indicates presence of intense pain, enabling quantitative analysis of the data. 19 A study suggested that a 33% decrease in pain represents a reasonable standard for determining that a change in pain is significant from a patient's perspective. 17 Also, according to the PCDT for chronic pain, a successful treatment for pain relief will be considered as one that reduces at least 50% of the pain score on the VAS.…”
Section: Pain Assessmentmentioning
confidence: 99%